Penerapan Metode COPRAS dan ENTROPY dalam Pemilihan Anggota Badan Pengawas Pemilihan Umum (BAWASLU) - Saidah Rizki Tanjung; Mesran Mesran; Sarwandi Sarwandi; Meryance V Siagian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The General Election Supervisory Agency (BAWASLU) is an election management institution that is tasked with overseeing the implementation of elections throughout the territory of the Unitary State of the Republic of Indonesia. Members of the General Election Supervisory Agency (BAWASLU) are those who have the ability to supervise and are not members of political parties. It is hoped that an effective recruitment process can attract BAWASLU members who really meet their needs. BAWASLU often faces difficulties in selection because it still uses a manual system. Therefore, it is necessary to make a decision support system so that the Chairperson of BAWASLU can give an assessment to each new BAWASLU member. The research carried out is to create a system that can provide consideration in making decisions about the selection of Bawaslu members. By using the Entropy method used to calculate the weighting of the criteria, and produce the reject rate as the main criterion, the Entropy method investigates the harmony in discrimination between a set of alternative value data on certain criteria described in the Decision Matrix (DM). While the COPRAS method is used for ranking, the effect of maximizing and minimizing the criteria on the evaluation results is considered separately. The selection of the best alternative is based on considering the ideal and anti-ideal solutions